PEMENUHAN HAK RESTITUSI KEPADA KORBAN TINDAK PIDANA - Ahmad Rizal Awwalludin Ramadhani; Ahmad Sholikhin Ruslie (Gapenas Publisher, 2022)
The concept of restitution is for the protection of victims of criminal acts as victims who are ignored in terms of fulfilling the rights that should be obtained. The problem that will be discussed in this research is how to regulate the concept of restitution regarding protecting victims of criminal acts in Indonesia. This study uses an informative juridical method. the institution is a compensation given to the victim by the perpetrator where it is a protection for the victim to fulfilling the rights of the victim. regulations regarding the restitution mechanism have not been fully regulated in the laws and regulations iso that it will be difficult for victims of criminal acts who will apply for restitution